Upaya Pencegahan Overkriminalisasi Tindak Pidana Kesusilaan (Studi Kasus Perkara No. 46/PUU-XIV/2016) - Widiyanti Dia Dia (Equality Before The Law, 2026)
Over-criminalization in morality crimes is a legal issue that can lead to human rights violations and legal uncertainty. This study aims to analyze efforts to prevent over-criminalization in morality crimes by examining the Constitutional Court Decision No. 46/PUU-XIV/2016. The approach used in this research is juridical-normative, employing legislative analysis and court rulings, supported by the perspectives of law enforcement officers in Sorong City. Based on legal and constitutional considerations, the state can prevent over-criminalization by rejecting the petition submitted by the applicant and ensuring that the formulation of legal norms, particularly those related to morality crimes, adheres to the principles of proportionality, legal certainty, and human rights protection. Furthermore, the state needs to review regulations that may lead to excessive criminalization and establish clear boundaries in legal interpretation to prevent an overly broad definition that could disproportionately restrict individual freedoms. Interviews with law enforcement officers indicate that both preventive and repressive measures are necessary to address over-criminalization. Preventive efforts include awareness campaigns and public education on the dangers of adultery, extramarital relationships, and the risks of sexually transmitted diseases. Meanwhile, repressive measures involve strengthening sanctions, penalties, and legal threats to create a deterrent effect for offenders and serve as a warning to the public against engaging in similar actions.